Paradigm in building corporate engagement of Budget and Finance Office Royal Thai Police - Chimoon, Puschareeya; Thavisin, Nathanon (Journal of Public Administration Chiang Rai Rajabhat University, 2022)
This research aims to study the corporate culture, nature of work and corporate engagement, and to study personal factors, corporate culture, and the nature of the work that affects the organization of public servants, police, office, budget and finance. National Police Office The sample size is calculated to represent 190 people using Taro Yamane’s formula. Described statistics are distributed in the form of frequency, percentage, average, and standard deviation. Inference statistics the statistics used in test analysis are T-test, F-test, and multivariate regression equation analysis. The results showed that 1) Personnel of the Office of Budget and Finance, The National Police Office, had an opinion on the corporate culture, nature of the work, and the overall commitment to the organization. 1) Personal factors include education levels, income per month, different impacts on the organization of public servants, police, office, budget and finance, 2) corporate culture, as well as: Corporate Features Corporate Leadership Features Personnel Management Conditions of Success 3) The nature of the work consists of a variety of tasks, the reflection of the work, the effect of the organization of the police, the office of the office, the budget and finance, the difference in the same direction.